Комунікативна політика в системі публічного управління - Вороніна, Юлія Євгенівна; Воронина, Юлия Евгеньевна; Voronina, Yuliia (My University, 2018)
UK: У статті проаналізовано апарат публічного управління. Визначено шляхи його розвитку та вдосконалення для підвищення якості надання публічних послуг, а також ефективного регулювання питань суспільного значення. Сучасний стан державного управління потребує вдосконалення та розвитку у напрямі вирішення суспільних проблем та налагодження комунікативних зв'язків із громадськістю для створення зворотного спілкування. Визначено критерії ефективності державного управління та соціальну спрямованість його подальшого розвитку й удосконалення. RU: В статье проанализирован аппарат публичного управления. Определены пути его развития и совершенствования для повышения качества предоставления публичных услуг, а также эффективного регулирования вопросов общественного значения. Современное состояние государственного управления нуждается в совершенствовании и развитии в направлении решения общественных проблем и налаживания коммуникативных связей с общественностью для создания обратного общения. При разработке государственной политики необходимо учитывать потребности общества и создать систему первоочередных заданий для неотложного решения. Повышение эффективности привлечения граждан до процессов государственного управления нуждается прежде всего развития организационной и политической культуры в регионах государства. В процессе исследования был выявлен комплекс связанных проблем с развитием и усовершенствованием аппарата государственного управления, а также найденная почва для дальнейших исследований в создании комплексной эффективной системы держаного управления с применением методики общественвенного развития и совершенствования для повышения качества предоставления публичных услуг, а также эффективного регулирования вопросов общественного значения. Современное состояние государственного управления нуждается совершенствования и развития в направлении решения общественных проблем и налаживания коммуникативных. EN: The vehicle of public management is analysed in the article. The ways of his development and perfection are certain for upgrading of grant of public services, and also effective adjusting of questions of community sense. The modern state of state administration needs perfection and development direction of decision of public problems and adjusting of communicative public relations for creation of reverse communication. At development of public policy it is necessary to take into account the necessities of society and create the system of near-term tasks for an urgent decision. The increase of efficiency of bringing in of citizens to the processes of state administration needs foremost development of organizational and political culture regions of the state. In the process of research the complex of the constrained problems was educed with development and improvement of vehicle of state administration, and also the found soil for further researches in creation of the complex effective system of management with application of methodology of public communication, social planning, mechanisms of modernisation of vehicle of government service within the framework of direction of integration. The criteria of efficiency of state administration and social orientation are certain him further development and improvement. Public politics is the basic constituent of democratic society, able to take into account interests of different community groups in the process of preparation and making decision government bodies. Communicative processes are an instrument in the hands of public politicians. Today public government bodies and political elite play the the communicative field for own the worked out rules, not having state strategy of political communications. Thus, at the terms of permanent democratization of society in a complex with modernisation of the system of government service developed the result of introduction of methodology of the sociocultural planning and the improved vehicle of state administration, that is fully sent to overcoming of near-term problems of society taking into account interests of all layers of population.
Communicative politics in the system of publik management
Keywords: державне управління; управлінський апарат; удосконалення; розвиток; государственное управление; аппарат управления; усовершенствование; развитие; governance; management apparatus; improvement; development